Effect of the clay ratio on the bearing capacity of road fills - Tuna, A. (My University, 1989)
A method is presented as to how to determine the optimum clay ratio. Samples from coarse grained material and clay are taken as typical soils. In this method, the mixture is compacted in a model form which can simulate various angles of slope and which is loaded almost at the top edge of the slope until the collapse load is obtained. Thus the mixture ratio which is the ultimate bearing capacity, is determined.
Zum Einfluss des Tongehaltes auf die Bruchlast von Erdfuellungen im Strassen- und Landebahnbau
Keywords: Granular Materials--Moisture Determination; Roads and Streets--Testing; Soils--Compaction; Collapse Load; Optimum Clay Ratio; Road Fills; Slope Angle; Clay